2022
DOI: 10.3345/cep.2021.01004
|View full text |Cite
|
Sign up to set email alerts
|

Psychological aspects in children and parents of children with chronic kidney disease and their families

Abstract: Pediatric chronic kidney disease (CKD) is a chronic illness that affects the overall quality of life of patients during childhood. This article highlights the psychological and social burden of CKD in patients and their families. Patients with CKD and their families require comprehensive treatment for psychosocial problems. Therefore, it is crucial for pediatricians to screen for these issues and refer patients and their families for therapy. Tools that are short, easy to administer, and easy to score, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Anxiety was present in 56 (72.7%) of patients while 21 (23.7%) had no anxiety. There was no much improvement in mood, aggression, depression or anxiety after starting dialysis unlike patient with renal transplant the complex care that children with CKD require [6].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Anxiety was present in 56 (72.7%) of patients while 21 (23.7%) had no anxiety. There was no much improvement in mood, aggression, depression or anxiety after starting dialysis unlike patient with renal transplant the complex care that children with CKD require [6].…”
Section: Resultsmentioning
confidence: 97%
“…During an evaluation, if problems such as anxiety, withdrawn behavior, low self-esteem, school refusal, attention deficit, poor scholastic performance, or poor treatment adherence are perceived or reported, the primary physician can refer the child to a mental health professional or a medical social worker for further evaluation. Warady and Chadha reported that therapeutic camps organized for children with kidney failure were successful, indicating reduced depression, improved selfesteem and self-confidence, and overall promotion of emotional maturity[6]. The patients with ESRD and RRT reported high levels of stress, depression, anxiety, mood changes, aggression, anger and feelings of hopelessness related to worries concerning their own health and the perception of their limitations.…”
mentioning
confidence: 99%
“…There is also an increased risk for the condition if mother, father or sibling has kidney failure. There is a wide range of symptoms for ESRD, which can often be confused as indications of other medical conditions [3].…”
Section: End-stage Renal Disease (Esrd)mentioning
confidence: 99%
“…Psychological preparation, mental health training and proper planning can help families cope and adjust to the condition at hand and can help with depression, selfesteem and self-confidence. 36 Additionally, the mode of KRT may have effects on neurocognition. Adolescents who undergo a renal transplant do fare better academically and can receive appropriate test scores in attention, language and visual-spatial domains compared to those on dialysis.…”
Section: Cognitive and Psychological Issues Of Ckdmentioning
confidence: 99%
“…Utilising interventions based on cognitive behavioural therapies, art, storytelling, music and games can help ease anxiety, depression and pain during the adjustment period. Psychological preparation, mental health training and proper planning can help families cope and adjust to the condition at hand and can help with depression, self‐esteem and self‐confidence 36 …”
Section: Puberty and Growth Considerationsmentioning
confidence: 99%